Spigelian hernia with bilateral undescended (impalpable) testis in a child: rare scenario - Singh, Gaurav; Singh, Garvita; Aggarwal, Satish K. (International Journal of Contemporary Pediatrics, 2021)
Spigelain hernia (SH) is rarely seen in children. Various mechanisms has been described for the co-existence with cryptorchidism. A 4 month old boy, a known case of bilateral impalpable testes and intermittent right lower abdominal swelling was brought to paediatric emergency with complaints of excessive cry, poor feeding and irreducible right lower abdominal swelling - the swelling was a little higher than the usual inguinal hernia. On exploration, SH was seen coming off the deep ring then turning around the conjoint tendon and dissecting between internal oblique and external oblique aponeurosis. The hernia contained oedematous but viable gut with compression over the testicular vessels. Gut was viable. The testes was mobilized and fixed into the scrotum. Left testis was impalpable for which nubbin excision was done at a later date. A SH in the lower abdomen may be confused with a high inguinal hernia. In acute obstruction, emergent exploration and reduction is the cornerstone of treatment.